Lack of Gαi2 leads to dilative cardiomyopathy and increased mortality in β1-adrenoceptor overexpressing mice - Keller, Kirsten (2015)
Aims Inhibitory G (Gi) proteins have been proposed to be cardioprotective. We investigated effects of Gαi2 knockout on cardiac function and survival in a murine heart failure model of cardiac β1-adrenoceptor overexpression. Methods and results β1-transgenic mice lacking Gαi2 (β1-tg/Gαi2 -/-) were compared with wild-type mice and littermates either overexpressing cardiac β1-adrenoceptors (β1-tg) or lacking Gαi2 (Gαi2 -/-). At 300 days, mortality of mice only lacking Gαi2 was already higher compared with wild-type or β1-tg, but similar to β1-tg/Gαi2 -/-, mice. Beyond 300 days, mortality of β1-tg/Gαi2 -/- mice was enhanced compared with all other genotypes (mean survival time: 363 ± 21 days). At 300 days of age, echocardiography revealed similar cardiac function of wild-type, β1-tg, and Gαi2 -/- mice, but significant impairment for β1-tg/Gαi2 -/- mice (e.g. ejection fraction 14 ± 2 vs. 40 ± 4% in wild-type mice). Significantly increased ventricle-to-body weight ratio (0.71 ± 0.06 vs. 0.48 ± 0.02% in wild-type mice), left ventricular size (length 0.82 ± 0.04 vs. 0.66 ± 0.03 cm in wild types), and atrial natriuretic peptide and brain natriuretic peptide expression (mRNA: 2819 and 495% of wild-type mice, respectively) indicated hypertrophy. Gαi3 was significantly up-regulated in Gαi2 knockout mice (protein compared with wild type: 340 ± 90% in Gαi2 -/- and 394 ± 80% in β1-tg/Gαi2 -/-, respectively). Conclusions Gαi2 deficiency combined with cardiac β1-adrenoceptor overexpression strongly impaired survival and cardiac function. At 300 days of age, β1-adrenoceptor overexpression alone had not induced cardiac hypertrophy or dysfunction while there was overt cardiomyopathy in mice additionally lacking Gαi2. We propose an enhanced effect of increased β1-adrenergic drive by the lack of protection via Gαi2. Gαi3 up-regulation was not sufficient to compensate for Gαi2 deficiency, suggesting an isoform-specific or a concentration-dependent mechanism.